If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2(x + -5) = -3 + 4x + 4 Reorder the terms: 4x + -2(-5 + x) = -3 + 4x + 4 4x + (-5 * -2 + x * -2) = -3 + 4x + 4 4x + (10 + -2x) = -3 + 4x + 4 Reorder the terms: 10 + 4x + -2x = -3 + 4x + 4 Combine like terms: 4x + -2x = 2x 10 + 2x = -3 + 4x + 4 Reorder the terms: 10 + 2x = -3 + 4 + 4x Combine like terms: -3 + 4 = 1 10 + 2x = 1 + 4x Solving 10 + 2x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 10 + 2x + -4x = 1 + 4x + -4x Combine like terms: 2x + -4x = -2x 10 + -2x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 10 + -2x = 1 + 0 10 + -2x = 1 Add '-10' to each side of the equation. 10 + -10 + -2x = 1 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 1 + -10 -2x = 1 + -10 Combine like terms: 1 + -10 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5
| -p-2=18-27p+6 | | 1650+x(145.50)=3250.50 | | 22c+17=11+3c | | 10=0.3x+9.1 | | -9x-7(0)=-30 | | 2x^4-4x^3-1x^2=0 | | 6=-5x+21 | | 36+3y=3y-24 | | 3t-t-8=t-8 | | 10=0.3k+9.1 | | 3=-14-4 | | x^3-3-5x+3=-3x^2+10 | | Log(-9-5x)=1 | | 4x+8-3x+7=x+7 | | 2.5p-4(p+7)=0 | | 4x-5(x+6)=1 | | 12x+9y=564 | | 6(4a-5)=-30-8a | | 53a+21=a | | 5p-4(9+7)=0 | | 5x=x+6 | | 2x=6x-3.4 | | 1=.25x-3 | | -2/3*-2/3-3/4(21/3)= | | -5(2p+2)-10=3(4p+8) | | h(x)=x^2-7x+6 | | (3+2i)(5-3i)=0 | | 4x^2-32=2x | | 6m-8=9m+1 | | x^2-9=-4*x+7 | | 0.66=log(x) | | 2cos^2x-6cosx-2=0 |